Cardiovascular Risk Factors in Acromegaly: What's the Impact of Disease Control? - Amado, Ana; Araújo, Fernando; Carvalho, Davide (Experimental and Clinical Endocrinology & Diabetes, 2018)
Objective Cardiovascular disease is one of the most important causes of death in acromegalic patients. The aim of this study is to compare the prevalence of cardiovascular risk factors among acromegalic patients and to evaluate the impact of disease control on these factors.Material and Methods 11 acromegalic patients with active disease and 12 controlled patients were evaluated for blood pressure, body mass index, glucose, coagulation status, and lipid profile. A group of 11 patients with non-functioning pituitary adenomas was used as control population.Results Significant differences were found in lipid profile, glucose and coagulation status in both active and controlled patients. Higher levels of fasting glucose (151.2±102.5 mg/dL, p=0.05 and 108.3±23.4 mg/dL, p=0.02 for active and controlled patients respectively) and fibrinogen (427.1±61.9 mg/dL, p=0.02 and 437.3±106.6 mg/dL, p=0.04 for active and controlled patients respectively) were present in both acromegalic groups. Active patients had higher levels of antithrombin III (1.1±0.1 U/mL, p=0.005) and the controlled ones had higher levels of high density lipoprotein cholesterol (56.1±12.5 mg/dL, p=0.05), compared with the non-functioning group. The differences between active and controlled acromegalic patients are that the latter have reduced total cholesterol (170.4±31.7 vs 201.7±34.6 mg/dL, p=0.02), lower density lipoprotein cholesterol (96,8±25,2 vs 130.8±31.5 mg/dL, p=0.01) and antithrombin III (1.0±0.2 vs 1.1±0.1 U/mL, p=0.05).Conclusion There is some reduction in cardiovascular risk factors with control of the disease, but possibly without the return to basal levels.
Keywords: Pituitary adenoma; Cardiovascular risk management; GH